Olympic Medals and Demo-Economic Factors: Novel predictors, the ex-host effect, the exact role of team size, and the "Population-GDP" model revisited - G. Vagenas; E Vlachokyriakou (Sport Management Review, 2012)
The present study revisited the problem of estimating Olympic success by critical demo-economic indicators. The sample consisted of the 75 winner countries at the Athens 2004 Olympic Games (not previously analyzed). Medal totals were log-linearly regressed on land, population, GDP, urban population, inflation, growth rate, unemployment, labor force, health expenditures, ex-host, and team size. Multiple regression assumptions were tested with proper diagnostics including collinearity. Olympic team size was the best single predictors of Olympic medals (R2 = 0.690, p < 0.001), and as an alternative criterion variable was significantly regressed on population, growth rate, health expenditure, and unemployment (R2 = 0.563, p < 0.001). Medal totals were significantly regressed on population, ex-host, health expenditure, growth rate, and unemployment (R2 = 0.541, p < 0.001). The classical population-GDP model extracted only 28% of the variance in total medals (R2 = 0.277, p < 0.001), and this was slightly improved when combined with unemployment (R2 = 0.365, p < 0.001). It appears that the size of the Olympic team plays the role of transmitting the composite impact of a country's size and economy to the end-phase of Olympic success. Winning Olympic medals depends on the combined potential of population, wealth, growth rate, unemployment, ex-host, and social-sport expenditures. Larger and wealthier countries win more medals by “producing” larger Olympic teams as a result of possessing more athletic talents and better support for social and sport related activities.